Improvement in time to multiple sclerosis diagnosis: 25-year retrospective analysis from New York State MS Consortium (NYSMSC). (May 2023) - Jakimovski, Dejan; Kavak, Katelyn S; Zakalik, Karen; Coetzee, Timothy; Gottesman, Malcolm; Coyle, Patricia K; Zivadinov, Robert; Weinstock-Guttman, Bianca
Judicious multiple sclerosis (MS) diagnosis and early start of disease modifying therapy significantly improves long-term disability outcomes in persons with MS (pwMS). Retrospective analysis based on 25-year New York State MS Consortium (NYSMSC) data determined the effect of changes in the respective diagnostic criteria in shortening the time between symptom onset to MS diagnosis. Based on 9378 current and historical MS cases, there was a significant decrease in time to diagnosis in pwMS from 1982–2001 to >2017 periods (average 4.2 vs. 1.1 years, p < 0.001). Additional improvements and better implementation of the MS diagnostic criteria can further decrease the diagnosis lag.